Factors affecting food waste at fast food restaurants in Kota Bharu, Kelantan. - Marimuthu, Logenthiran; Naga, Merom; Michelle Lee, Yueh Jia; Ghani, Mohammad Aman (2015)
The objective of this study is to examine the relationship between three independent variables which is kitchen management, over serving and menu design as our independent variables and food waste in fast food restaurants is our dependent variable. The data were collected from 250 respondents and there were 244 data were valid. The correlation coefficient for kitchen management and food waste is 0.463, the correlation coefficient for over serving and food waste is 0.342 and the correlation coefficient for menu design and food waste is 0.470. It means all the correlation coefficient which is positive and weak. The result indicates that all correlation coefficient at P=0.0000. Therefore, there is a significant relationship between kitchen management, over serving and menu design and food waste in fast food restaurant. Thus factors that affecting food waste in fast food restaurants are kitchen management, over serving and menu design.